FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU IBU RUMAH TANGGA DALAM PENCEGAHAN PENYAKIT LEPTOSPIROSIS PADA KELUARGA DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KECAMATAN TEMBALANG - Windayani Sitindaon; Syamsulhuda B Mustofa; Besar Tirto Husodo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Background: Leptospirosis disease is an infectious disease of animals caused by the Leptospira bacteria. This disease is a widespread zoonotic in the world, especially in tropical regions including Indonesia. The family plays an important role in maintaining the environment, and contributes actively in the prevention and eradication of disease sources, especially mothers who play an important role in protecting the family from exposure to disease. The aim of this research is to analyse factors affecting the behavior of housewives in the prevention of leptospirosis disease in families. Method: This type of research is descriptive analytic, quantitative approach, cross sectional research design with a sample number of 96 respondents (housewives residing in the work area Puskesmas Kedungmundu). The instruments used are questionnaires with interviews. Analysis of the data used are univariate and bivariate with Chi-square test. Results: Research shows the age of respondents dominated by age ≥ 45 years with the last education graduated high school/equivalent. Respondents did not work for 62.5%. The results showed that the level of education (p = 0,006), knowledge (p = 0,027), the perception of vulnerability (p = 0,027) and the perception of benefits (p = 048) related to housewives ' behaviour in the prevention of leptospirosis disease in families. The age variable of the respondent (p = 0,142), the work (p = 0,605), the perception of seriousness (p = 0,889) and the perception of inhibitions (p = 0,747) are not related to housewives ' behavior in the prevention of leptospirosis disease in the family. Education and employment part of the modification components do not affect the behavior directly, but affect the individual beliefs. Conclusion: The community should be more cautious in maintaining a pet in the home because it can transmit leptospirosis disease for anyone.